Overview of Sports-Related Knee Injuries Managed Operatively at RSU Haji Medan in 2023 - Destriani Farizka Siregar; Mohammad Shahreza; Heri Gunanti Surbakti; Anandhika Dwijaya (UMSU, 2026)
Abstract: Introduction: Knee injuries are one of the sports-related injuries that frequently require operative management. The prevalence of knee injuries is 9%, with 48 cases per 1000 patients involving ACL injuries. Methods: This study used a quantitative descriptive method with a cross-sectional design. Data were collected from medical records and interviews using the Indonesian-International Knee Documentation Committee (I-IKDC) questionnaire. Results: From 33 patients, the majority were aged 19–44 years (90.9%), male (87.9%), and most injuries occurred during soccer (30.3%). The most common type of injury was ACL injury (75.8%). The mean I-IKDC score was 62.6 with a standard deviation of 9.1, with a minimum score of 49.4 and a maximum score of 82.7. Conclusion: Sports-related knee injuries predominantly occurred in males of productive age, especially while playing soccer, with ACL injuries as the most frequent type. Postoperative knee function was in the moderate category